Identification of Bipolaris maydis race T pathogenic to Populus deltoides - B.N. PANDEY2, S. CHAUHAN1 and (Indian Phytopathology, 2002)
Isolates of Bipolaris maydis pathogenic to Populus deltoides were identified to be race T on the basis of their virulence to certain male-cultivars of the host from Texas provenance, toxin production, sclerolia formation, light pigmentation and poor sporulating potency on the culture media under controlled conditions.